Calculated dietary glycemic index, glycemic load and incidence of gestational diabetes mellitus in healthy pregnant women - Hasbullah, Farah Yasmin (2016)
The role of dietary glycemic index (GI) and glycemic load (GL) intake in GDM incidence is uncertain. This prospective cohort study was conducted to determine the contribution of calculated dietary GI and GL towards the incidence of GDM among healthy pregnant women in Seremban district. Pregnant women were recruited in the first trimester and were followed-up until their second trimester. GDM was diagnosed during the second trimester of pregnancy using International Diabetes in Pregnancy Study Groups (IADPSG) criteria. Primary outcome was GDM incidence whereas calculated dietary GI and GL were the primary independent variables. Dietary intake and selected established risk factors including maternal age, ethnicity, family history of diabetes mellitus (DM), history of GDM, and pre-pregnancy body mass index (BMI) acted as covariates to dietary GI and GL. These risk factors were obtained through interviews or medical records. Food intake, dietary GI and GI were assessed using food frequency questionnaire (FFQ). Independent t-test was used to compare the differences between GDM and non-GDM respondents. Binary logistic regression was used to determine the contribution of calculated dietary GI and GL towards GDM incidence. The number of respondents recruited was 347, with a response rate of 78.9%. Data analysis was performed for respondents who completed the assessments during the second trimester (n = 294). In this cohort, the incidence of GDM was 11.6%. GDM respondents tended to have a history of GDM and be overweight or obese. GDM respondents had significantly lower carbohydrate, dietary GI and GL intakes during the first trimester. Dietary GI and GL intake during the first trimester significantly predicted GDM incidence in a crude odds ratio. After adjusting for confounders, only dietary GI intake during the first trimester was a significant contributor towards GDM incidence; however, the association was negative (β = -0.186, OR 0.830, p = 0.035). The negative relationship could possibly be due to dietary misreporting or the invalidity of the method used in assessing dietary GI intake. Dietary GL was positively associated with GDM incidence during both trimesters, but the association was not significant. In conclusion, dietary GI significantly contributed towards GDM incidence, in addition to other established risk factors including pre-pregnancy BMI and history of GDM. However, failing to demonstrate positive links between dietary GI intake and GDM incidence was unexpected which warrants future investigation.